(untitled) (LACCEI, 2024)
In this research, the gold and silver extraction process was evaluated from a refractory gold-silver sulfide originating from the Gran Chimú Province in the La Libertad department of Peru. The extraction process was carried out in two stages. The first stage was called indirect bio-oxidation, and in the second stage, a conventional cyanidation process was performed. In the first stage, acid water from the area was used to culture the Thiobacillus ferrooxidans bacteria. The culture was promoted by adding salts called 9K, and the aim of this stage was to transform ferrous cations to ferric cations, as evidenced by the color change of the acid water to red. In the second stage, a solution of sodium cyanide and calcium oxide (quicklime) was used, and the total cyanidation time was 51 hours at an average pH of 10.5 at room temperature. The dry quantification process of gold and silver used was a fire assay. The extraction process variables evaluated were the concentration (0, 0.75, and 1.5) mg/g of silver salt, mineral particle size (80% less than 100 mesh, 80% less than 200 mesh, and 80% less than 325 mesh), and the temperature of indirect bio-oxidation (25, 45, and 65)ºC. To evaluate the effect of the bio-oxidation pre-treatment, conventional cyanidation tests were carried out, resulting in extraction percentages of 44.61% and 48.98% for gold and silver, respectively, with a particle size of 80% less than 325 mesh. This indicated the need to implement the aforementioned pre-treatment to release the gold and silver from the mineral. The extraction percentages using both stages were 61.44% for gold (80% less than 325 mesh 65ºC 0.0 mg/g) and 94.24% for silver (80% less than 200 mesh 65ºC 0.75 mg/g) at best, and 35.98% for gold (80% less than 100 mesh 45ºC 0.0 mg/g) and 41.44% for silver (80% less than 100 mesh 25ºC 0.0 mg/g) as the lowest recorded values.